Climate change adaptation and the German economy - Ulrike Lehr; Anne Nieters; Thomas Drosdowski (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2015)
Although climate change is a global challenge, its effects occur locally and differ by region. A feasible adaptation strategy needs to assess regional damages and their socio-economic effects. For Germany, the largest threat comes from extreme weather events, which will impact residential and commercial buildings, infrastructure and in the case of heat waves will limit labor productivity. This paper presents findings from a study of economic effects of climate change adaptation until the year 2050 in Germany on different scales. In particular, the authors have applied an input-output-based macroeconometric model, adjusting it to cope with the challenges of damages from heat waves, and river flood events, by integrating suitable adaptation measures to such events into the model. Infrastructure damages, shifts from domestic production to imports, and low levels of productivity due to heat waves, are some of the topics the paper deals with. Comparing scenarios with (a) integrated extreme weather events and (b) adaptation measures with a reference scenario without extreme weather or adaptation, the simulation results reveal slightly negative effects on economic sectors and Germany's economy as a whole. These effects intensify over time and hurt the economy. Adaptation measures reduce the damages and pay off, but the economy is still worse off with climate change.
Keywords: Q54; 330; extreme weather events; heat wave; river flood; adaptation